Upaya Sekolah Dalam Mengembangkan Akhlak Islami Siswa Melalui Program Bina Pribadi Islami (BPI) Di SMP IT Taqiya Rosyida Surakarta - Fatkha Atika Rahmah; Very Aulia Rahman; Mahayoni Zaenab Satrianing Khotimah; Naufal Rafi’i Ahmad Riza; Taqiyuddin Zaky (Universitas Muhammadiyah Sorong, 2025)
Moral education in Indonesia faces significant challenges in ensuring the relevance of educational programs to students' character, particularly as modern students experience moral decline. Generally, character education programs in schools tend to be very general in scope; however, SMP IT Taqiya Rosyida adopts a unique approach by developing the Islamic Character Building (BPI) program. This study aims to determine the impact of the BPI program on students' character development. Using a descriptive qualitative method, this research involved in-depth interviews with school representatives and students at SMP IT Taqiya Rosyida to obtain comprehensive data. The results show that the Islamic Character Building program significantly contributes to the development of students’ morals, improved behavior, and personal growth.